Comparative Analysis of Length of Stay and Cost-effectiveness in Typhoid Patients Treated with Cephalosporins and Fluoroquinolones - Yudith Yunia Kusmala; Melly Safitri Indriani; Desy Linasari (Global Medical & Health Communication (GMHC), 2025)
Typhoid fever is an infectious disease caused by the bacterium Salmonella typhi (S. typhi). Hospitals often experience financial losses in treating typhoid fever patients, as the costs exceed the satisfaction provided by the National Health Insurance (Jaminan Kesehatan Nasional, JKN), administered by the Social Security Agency for Health (Badan Penyelenggara Jaminan Sosial, BPJS Kesehatan). This study aimed to evaluate treatment duration and the cost-effectiveness of cephalosporins (ceftriaxone) versus fluoroquinolones (levofloxacin) therapy in adult patients with typhoid fever. This research employs an observational, analytical, cross-sectional design. The data consist of secondary data obtained from the medical records of patients diagnosed with typhoid fever between January 1, 2022, and December 31, 2022, in the adult inpatient ward at Dustira Military Hospital in Cimahi. The study included a total of 162 individuals who met the specified inclusion criteria. We employed the Mann-Whitney test to evaluate the data. The study found that patients with typhoid fever treated with fluoroquinolone antibiotics had a shorter average length of stay (ALOS) of 3.69±0.86 days compared to those treated with cephalosporin antibiotics, whose ALOS was 4.35±1.15 days, with a p-value of 0.000. The difference in ALOS between the two groups was statistically significant. The average total cost for patients who received fluoroquinolone antibiotics was lower (IDR 2,273,213.01) compared to patients who received cephalosporin antibiotics (IDR 2,524,729.11), with a p-value of 0.000. This study concluded that fluoroquinolone therapy is more effective than cephalosporins in reducing the duration of hospitalization among patients with typhoid fever. Accordingly, intravenous fluoroquinolones may be considered as a treatment option to help shorten hospital stay.